Recomposition du paysage sportif d’une ville du Sud : le paradoxe des nouveaux lieux de pratiques sportives à Ouagadougou - Aude Nikiema (Projets de Paysage)
The road network is a founding element in the construction of the urban landscape. In Northern countries, it is the object of a reorganisation of the landscape based on urban policies intended to reduce the negative external impacts of such a reorganisation. Whereas the construction of cities in the South is based on an appropriation of the logic of urban planning documents as conceived by Western countries, how does the spontaneous emergence of sporting practices fit into the landscape? To answer this question, places where sports are practised were geolocated in Ouagadougou, the capital of Burkina Faso, and surveys were carried out with 154 sportsmen and women, 10 of whom were interviewed in depth. In this city, these activities take place informally on urban sites that are not equipped for sports. There is no specific practice, but the study of the subject based on the notion of the landscape has revealed a particularity which is that sports are practised along roadsides. Of no interest as landscapes, these areas nevertheless attract people. Their disadvantages, such as accident risks and pollution, although perceived by the users, are not an obstacle to their use. The positive perception of these spaces is based on their material advantages, such as accessibility, surfacing and lighting, and their social advantages in terms of frequentation and social interaction.